Focal therapy for prostate cancer: patient selection and evaluation. Issue 1 (January 2012) - Gravas, Stavros; Tzortzis, Vassilios; de la Riva, Santiago Isorna Martinez; Laguna, Pilar; de la Rosette, Jean
Recent stage migration toward low-risk prostate cancer, overtreament of biologically insignificant tumors with radical prostatectomy at the additional expense of a non-negligible morbidity and undertreatment of patients improperly selected for active surveillance are the main reasons that have fuelled the concept of focal therapy. Optimal selection of patients is the key for the successful implementation of focal therapy. Selection criteria for focal therapy vary widely and depend on clinical, histological and imaging characteristics of the patients that are highlighted in this article. In addition, the rationales, merits and limitations of the available methods for the assessment of potential candidates, the evaluation of treatment efficacy and follow-up of these patients are discussed.